MOISTURE CONTENT AND THERMAL BALANCE DURING COMPOSTING OF FISH, BANANA MULCH & MUNICIPAL SOLID WASTES - El Zein, Aya; Seif, Hamdy; Gooda, Essam (European Scientific Journal, ESJ, 2015)
Temperature, moisture content, oxygen concentration in the airspace, and C/N ratio are the primary factors affecting the composting process (Haug, R. T. 1993; Ekinci, K., Keener, H.M., & Elwell, D.L. 2002). The overall aim of this study is to understand the effect of composting different types of wastes with different weights on temperature and moisture content during composting. The experimental trials involve an aerobic composting of fishery house wastes, municipal solid waste, banana plantations wastes and composted meat. Waste mix ratios were adapted following Carbon to Nitrogen formula. The compost material was left for more than 29 days of which more than 24 days of decomposition in barrel followed by 5-7 days piled up in open ground space and covered with nylon bags. Temperature at two depths 25 cm and 50 cm of top compost surface and moisture content were monitored throughout the experiments to control turnover frequency and water addition. A rapid increase in temperature was noticed indicating a marked microbial activity. There was a significant correlation between the moisture content and the temperature distribution within the pile. Higher temperature can be obtained by increasing size of the composting material or increasing volumetric mixing ratios of compost substrates or by trying other combinations with higher C/N ratios.